Economic Development and Climate Change: Insights from Religious Countries - Agusalim, Lestari; Karim, Muhamad; Irfany, Mohammad Iqbal; Lestari, Aprima Vista Ajeng; Pebrianti, Herlina (International Journal of Energy Economics and Policy, 2025)
Among the most pressing environmental challenges, climate change is anticipated to pose the highest global threat in the coming decade. This research examines the impact of political economic development on per capita CO2 emissions in 29 countries with state religions, applying the frameworks of Environmental Kuznets Curve (EKC) and Pollution Haven Hypothesis (PHH). Employing the Panel Autoregressive Distributed Lag (PARDL) model, the study analyzes data from 1990 to 2022, incorporating both time series and cross-sectional information. The model’s robustness is verified by replacing CO2 emissions per capita with ecological footprint per person. Results indicate that the EKC hypothesis is not supported in most nations, particularly low-income countries still heavily dependent on fossil fuels. In contrast, the PHH hypothesis is confirmed over the long term, with foreign direct investment (FDI) inflows contributing to increase per capita CO2 emissions, especially in countries with lax environmental regulations. Energy consumption and industrial sector contributions significantly affect emissions, while renewable energy consistently reduces CO2 output. Furthermore, democratic political systems are associated with higher emissions, particularly in rapidly growing economies. The study suggests implementing faith-based and sustainability-oriented approaches, such as a faith-driven economy that incorporates spiritual values into green economic policies. Additionally, faith-based investing is recommended to encourage ethical and environmentally responsible business practices. These strategies aim to help countries with official religions strike a balance between economic growth and environmental conservation in the face of climate change.